1970
DOI: 10.2172/4148916
|View full text |Cite
|
Sign up to set email alerts
|

Results of Sefor Zero Power Experiments.

Abstract: The SEFOR experimental program is comprised of a series of tests beginning with low power tests, proceeding through static and frequency response tests at various power levels up to full power, and culminating in a series of sub-prompt and super-prompt critical transients. The results of the low (zero) power tests are reported here and are compared with calculations. The agreement between experiment and calculation is generally good. The tests were conducted at low power and included such experiments as the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Comparison of the results with calculations demonstrated that the Doppler component of the feedback can be described by a fuel temperature coeffic1~nt T(dk/dT) of ~.0081 with an estimated standard deviation of ±0.0014. This coefficient compares favorably with the value* of ~.0085 that was predicted 2 prior to the measurements. * This is the estimated predictiOn for ·the cores, Assemblies 1-1 and 1-J (the present core), on which these Doppler experiments were performed.…”
Section: Discussion Of Resultssupporting
confidence: 64%
“…Comparison of the results with calculations demonstrated that the Doppler component of the feedback can be described by a fuel temperature coeffic1~nt T(dk/dT) of ~.0081 with an estimated standard deviation of ±0.0014. This coefficient compares favorably with the value* of ~.0085 that was predicted 2 prior to the measurements. * This is the estimated predictiOn for ·the cores, Assemblies 1-1 and 1-J (the present core), on which these Doppler experiments were performed.…”
Section: Discussion Of Resultssupporting
confidence: 64%
“…It is therefore important to consider the magnitude of the error in the Doppler coefficient as such in addition to a comparison of AkD, (7). Table III Table III.…”
Section: The Temperature Dependence Of the Doppler Coefficientmentioning
confidence: 99%